2016
DOI: 10.1136/sextrans-2015-052285
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel microbes associated with pelvic inflammatory disease and infertility

Abstract: ObjectivesAs pelvic inflammatory disease (PID) aetiology is not completely understood, we examined the relationship between select novel bacteria, PID and long-term sequelae.MethodsFastidious bacterial vaginosis (BV)-associated bacteria (Sneathia (Leptotrichia) sanguinegens, Sneathia amnionii, Atopobium vaginae and BV-associated bacteria 1 (BVAB1)), as well as Ureaplasma urealyticum and Ureaplasma parvum were identified in cervical and endometrial specimens using organism-specific PCR assays among 545 women en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
113
0
20

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(147 citation statements)
references
References 28 publications
4
113
0
20
Order By: Relevance
“…27 Morphologically, this species is similar to Mobiluncus and in fact many communities previously identified by microscopy as having Mobiluncus may actually have been colonized by BVAB1. 28 In addition to its association with bacterial vaginosis in general, BVAB1 was closely correlated with the presence of a positive “whiff” test in women with bacterial vaginosis, indicating the presence of volatile amines.…”
Section: Discussionmentioning
confidence: 70%
“…27 Morphologically, this species is similar to Mobiluncus and in fact many communities previously identified by microscopy as having Mobiluncus may actually have been colonized by BVAB1. 28 In addition to its association with bacterial vaginosis in general, BVAB1 was closely correlated with the presence of a positive “whiff” test in women with bacterial vaginosis, indicating the presence of volatile amines.…”
Section: Discussionmentioning
confidence: 70%
“…For these studies, we selected bacterial species commonly found in the human FRT, including a sexually transmitted pathogen, N. gonorrhoeae, and two endogenous vaginal microbes, one of which (L. crispatus) is commensal and the other of which (G. vaginalis) is associated with BV (18,19,33,55). It should also be noted that both N. gonorrhoeae and G. vaginalis are associated with endometritis and PID (2,20,21,55,56). Our results first showed that all tested species are capable of adhering to the 3-D EEC aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…Atopobia are normal colonisers of the human oral cavity and vaginal tract, where they play a role in the pathogenesis of bacterial vaginosis 6. There is also compelling evidence that they play a role in more invasive genital tract infections, including pelvic inflammatory disease,7 endometritis8 and tubo-ovarian abscesses 9. Bacteraemia, though rare, has been described in several species, including a case of Atopobium rimae in a patient with aspiration pneumonia10 and the recently described A. deltae in a patient with Fournier’s gangrene 11.…”
Section: Discussionmentioning
confidence: 99%